Some Observations on the Behavior of Soft Clay Under Undrained Cyclic Loading - Shahin, Mohamed; Loh, Richard; Nikraz, Hamid (Taiwan Geotechnical Society, 2011)
This note presents the results of a series of cyclic loading triaxial tests under undrained conditions that examines the effectiveness of consolidation history on reconstituted soft clay. For any particular consolidation history, the experimental results confirm the concept of the critical stress level of repeated deviator stress below which a state of non-failure stress equilibrium exists and above which effective stress failure occurs. However, an interesting finding of this study is that for heavily over-consolidated clay, both the state of stress equilibrium (below the critical stress level) and state of effective stress failure (above the critical stress level) develop at the very first few cycles of loading.